ISCHAEMIC HEART DISEASE AND GLYCAEMIC CONTROL IN TYPE-2 DIABETES MELLITUS BY QUESTIONNAIRE METHOD - TR, Yathish; Annamalai, Nachal; Shankar, Vinutha (Pakistan Journal of Physiology, 2010)
Background: Various tests like Echocardiogram, Nuclear scan, Electron-beam computed tomography, Coronary angiography, and magnetic resonance angiography are available for diagnosis of ischemic heart disease (IHD). But most of these are expensive, invasive and cannot be afforded in developing countries. An attempt was made to study sensitivity, specificity, and predictive value of non-invasive technique like questionnaire method and compared with traditional clinical evaluation. This study compared diagnosis of angina made with the Rose Questionnaire to diagnosis by physician in type-2 diabetes mellitus and the effect of glycaemic control. Methods: A cross-sectional study was done from March 2005 to March 2006. Cases were collected from outpatients and inpatients visiting RL Jalappa hospital and SNR Hospital attached to Sri Devraj Urs Medical College Kolar, Karnataka, India. Glycosylated haemoglobin levels were estimated. Data on Rose questionnaire angina and physician diagnosed angina were collected and compared between groups of well controlled diabetics, poorly controlled diabetics and controls. The 12 lead Electrocardiogram was used to confirm the diagnosis. Results: The Rose questionnaire had 63.63% sensitivity, 97.5% specificity, 73% positive predictive value, and 96% negative predictive value. This study also showed the occurrence of IHD was higher in the poorly controlled diabetics (16.3%) as compared to well controlled diabetic patients (6%) and controls (5%) which were significant. Conclusions: The questionnaire diagnosis showed good sensitivity and high specificity as compared with diagnosis by physicians. The questionnaire method can be frequently used and incorporated in cardiovascular risk assessment and epidemiologic screening programs.